Micropipette aspiration reveals differential RNA-dependent viscoelasticity of nucleolar subcompartments - Holly H. Cheng; James V. Roggeveen; Huan Wang; Howard A. Stone; Zheng Shi; Clifford P. Brangwynne (Proceedings of the National Academy of Sciences, 2025)
The nucleolus is a multiphasic biomolecular condensate that facilitates ribosome biogenesis, a complex process involving hundreds of proteins and RNAs. The proper execution of ribosome biogenesis likely depends on the material properties of the nucleolus. However, these material properties remain poorly understood due to the challenges of in vivo measurements. Here, we use micropipette aspiration (MPA) to directly characterize the viscoelasticity and interfacial tensions of nucleoli within transcriptionally active Xenopus laevis oocytes. We examine the major nucleolar subphases, the outer granular component (GC) and the inner dense fibrillar component (DFC), which itself contains a third small phase known as the fibrillar center (FC). We show that the behavior of the GC is more liquid-like, while the behavior of the DFC/FC is consistent with that of a partially viscoelastic solid. To determine the role of ribosomal RNA in nucleolar material properties, we degrade RNA using RNase A, which causes the DFC/FC to become more fluid-like and alters interfacial tension. Together, our findings suggest that RNA underlies the partially solid-like properties of the DFC/FC and provide insights into how material properties of nucleoli in a near-native environment are related to their RNA-dependent function.